Reactive Barrier Films - Yang, Ch.; Nuxoll, E.E.; Cussler, E.L.
Immobile reactive groups within films used as packaging materials can retard transport of solutes like oqgen and water vapor. A theory developed for these films shows that these groups do not affect the steady-state transport across the film, but that they do increase the time before permeability begins. The theory is verified by experiments with acid bam.ers made of polyvinylalcohol containing colloidal zinc oxide. These results imply that the time that bam'erpolymers are effective can be increased about two orders of magnitude, When reactive groups are combined with impermeable flakes, this time can be increased about three orders of magnitude. For example, a polymer bam'er currently effective for one hour can be made effective for over one year.